Interpretation of biomembrane structure by Raman difference spectroscopy. Nature of the endothermic transitions in phosphatidylcholines. - Gaber, B P (1978)
Raman difference spectroscopy has been applied to aqueous dispersions of dipalmitoyl phosphatidylcholine (DPPC). Difference spectra have been created by computer subtraction of absolute Raman spectra taken in each of three different temperature ranges: below the endothermic pretransition at 34 +/- 2 degrees C; between this temperature and the melting transition at 42 degrees C; and above the melting temperature. The resultant difference spectra are both quantitatively and qualitatively different, indicating that a distinct phospholipid conformation occurs in each of the three temperature ranges. Furthermore, the difference spectra show details of Raman spectral changes with greater clarity than is possible with conventional Raman techniques. A description of the lateral interchain order and the longitudinal chain order is given for each of the three temperature ranges. In addition to obtaining a more precise quantitative measurement of the changes in the Raman spectra, we observed some significant and previously unreported changes. It is suggested that distortion in the hexagonal lattice below the pretransition temperature previously reported by X-ray diffraction techniques may be responsible for interchain interactions which give rise to a Raman band observed only in the triclinic lattice of even-numbered n-alkanes.